2021
DOI: 10.1002/ana.26017
|View full text |Cite
|
Sign up to set email alerts
|

CaVα2δ Autoimmune Encephalitis: A Novel Antibody and its Characteristics

Abstract: Objective Discovery of a novel antibody would enable diagnosis and early treatment of autoimmune encephalitis. The aim was to discover a novel antibody targeting a synaptic receptor and characterize the pathogenic mechanism. Method We screened for unknown antibodies in serum and cerebrospinal fluid samples from autoimmune encephalitis patients. Samples with reactivity to rat brain sections and no reactivity to conventional antibody tests underwent further processing for antibody discovery, using immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Conversely, the adult patient succumbed to septic shock during postoperative management. The authors revealed that anti-CaVα2δ antibodies interfere with the tight coupling of calcium channels and sensors, leading to reduced neurotransmitter release from the presynaptic nerve terminals and decreased excitatory postsynaptic currents and inhibitory postsynaptic currents [5]. This supports the role of CaVα2δ subunits of VGCCs as autoantigens in AE.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Conversely, the adult patient succumbed to septic shock during postoperative management. The authors revealed that anti-CaVα2δ antibodies interfere with the tight coupling of calcium channels and sensors, leading to reduced neurotransmitter release from the presynaptic nerve terminals and decreased excitatory postsynaptic currents and inhibitory postsynaptic currents [5]. This supports the role of CaVα2δ subunits of VGCCs as autoantigens in AE.…”
Section: Discussionmentioning
confidence: 71%
“…Lee et al [5] was the rst to report on the pathogenicity of anti-CaVα2δ AE in 2021, which included two patients (one adult and one paediatric case) exhibiting typical AE features, such as memory loss, psychiatric symptoms, and seizures. The adult case was diagnosed with paraneoplastic syndrome due to neuroendocrine carcinoma, while the paediatric case was diagnosed with prior meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021 autoantibodies of the IgG2 subclass targeting an auxiliary subunit of presynaptic voltage-gated calcium channel (VGCC or Ca V ), α-2/δ subunit (Ca V α2δ) were found in two patients by screening serum- and CSF samples from seronegative AE patients [ 89 ]. The two patients presented with subacute cognitive decline, altered behavior, seizures and decreased consciousness.…”
Section: Autoantibodies With Extracellular Targetsmentioning
confidence: 99%
“…In cultured rat hippocampal neurons, binding of autoantibodies to the Ca V α2δ subunit of VGCC weakened the coupling of VGCCs and exocytosis, suggesting that the autoantibodies inhibit neurotransmitter release. Whole cell-recording of cultured rat hippocampal neurons showed that autoantibodies impaired neuronal excitatory and inhibitory postsynaptic current frequencies, potentially by interfering with the tight coupling of Ca 2+ channels and Ca 2+ sensors [ 89 ]. These findings needs to be validated, and warrant further research to evaluate the pathogenicity of IgG2 autoantibodies against Ca V α2δ.…”
Section: Autoantibodies With Extracellular Targetsmentioning
confidence: 99%